Facile donor (D)-π-D triphenylamine-based hole transporting materials with different π-linker for perovskite solar cells. (1st January 2020) - Li, Maohui; Ma, Shuang; Mateen, Muhammad; Liu, Xuepeng; Ding, Yong; Gao, Jing; Yang, Yi; Zhang, Xianfu; Wu, Yahan; Dai, Songyuan
Graphical abstract: The hole transporting materials with carbazole as π-linker exhibit better performance in perovskite solar cells than that of fluorene and biphenyl counterparts. Moreover, carbazole-based molecule shows comparable efficiency and extremely lower laboratory synthesis cost than conventional spiro-OMeTAD. Highlights: Facile hole transporting materials with varying π-linker are prepared. π-linker variation on photovoltaic properties are comprehensively investigated. Carbazole-based molecules show best performance in perovskite solar cells. Abstract: Three simple donor (D)-π-D triphenylamine-based hole transporting materials with biphenyl, fluorine or carbazole derivative as π-linker are prepared by facile process. The π-linker variation of investigated compounds on optical, electrochemical, thermal, hole mobility properties as well as photovoltaic properties in devices are comprehensively investigated. It is found that the molecule with carbazole and biphenyl π-linker exhibits obviously better hole mobility than that of fluorene counterpart, resulting in better hole extraction capacity at perovskite/HTM interface. When used in perovskite solar cells, carbazole-based molecule exhibits higher efficiency than biphenyl and fluorene-counterparts, which is even comparable to conventional spiro-OMeTAD. Although fluorene-based molecule also owns suitable HOMO level with respect to perovskite, lowest hole mobility limits photovoltaic performance in devices. This work demonstrates that carbazole unit own better application potential than that of fluorene and biphenyl for efficient perovskite solar cells.